Still born - Nettel, Guadalupe, 1973- (Bloomsbury Publishing, 2023)
"Alina and Laura are independent and career-driven women in their mid-thirties, neither of whom have built their future around the prospect of a family. Laura is so determined not to become a mother that she has taken the drastic decision to have her tubes tied. But when she announces this to her friend, she learns that Alina has made the opposite decision and is preparing to have a child of her own. Alina's pregnancy shakes the women's lives, first creating distance and then a remarkable closeness between them. When Alina's daughter survives childbirth--after a diagnosis that predicted the opposite--and Laura becomes attached to her neighbor's son, both women are forced to reckon with the complexity of their emotions, their needs, and the needs of the people who are dependent upon them"--